Representing Violence against Women in Latin American Media - Martínez Toledo, Yanet (2019)
Violence against women (VAW) in Latin America is a systemic issue. Even though in the last three decades some policies have discussed and improved women’s rights in the region, Latin America is still one of the most dangerous places in the world for women: 14 of the 25 countries with the highest rates of femicide in the world are in Latin America. According to Gender Equality Observatory (GEO), 2,559 women were victims of femicide in 2017. El Salvador (10), Honduras (6), Belize (5), Trinidad and Tobago (3), Guatemala (3), and the Dominican Republic (2) were the countries with the highest prevalence of femicide in the region (GEO, 2019).